Detection of cockroach faeces: consumption of fluorescent bait and production of UV‐light‐detectable faeces from German cockroach, Blattella germanica. Issue 3 (17th April 2015) - Varadínová, Zuzana; Frynta, Daniel; Aulický, Radek; Stejskal, Václav
Abstract Cockroaches have long been recognized as a major source of allergens in the human environment. As some allergens produced by cockroaches are accumulated within their tiny faeces and may persist unseen in the environment, development of a reliable method for monitoring cockroach faeces distribution and abundance is crucial. Our aim was to explore the rate of consumption of fluorescent bait and defecation of UV‐light‐detectable fluorescent faeces from Blattella germanica (L.) (Blattodea: Ectobiidae) as a prerequisite for the establishment of faeces monitoring in the field. Laboratory experiments revealed that (1) the fluorescent bait was accepted by cockroaches as a food source and faeces produced after its consumption were fluorescent as well; (2) there was a positive relationship between the fluorescent bait consumed and production of fluorescent faeces; (3) single and brief consumption of fluorescent bait led to continuous fluorescent faeces production, giving cockroaches enough time (ca. 27 h) to deposit fluorescent faeces in an entire area of cockroach activity as well as in shelters. The amount of fluorescent bait consumed and the amount of fluorescent faeces produced was nevertheless different among males, non‐gravid females, and gravid females. We subsequently validated the new fluorescent faeces‐based monitoring technique in a semi‐field experiment with human observers, which revealed that fluorescent faeces were reliably identified and distinguished from environmental dirt when illuminated with a UV flashlight. We further discuss the biological perspectives of our findings and recommendations for practical use.